Naturally occurring labdane diterpene and benzofuran from Globba pendula. - Maulidiani, H.M; Shaari , Khozirah; Paetz , ChristiaN; Stanslas, Johnson; Abas, Faridah; Lajis, Nordin (Natural Product Communications, 2009)
Phytochemical investigation on Globba pendula resulted in the isolation of a new naturally occurring 16-oxo-(8)17-12-labdadien-15,11-olide 1 and benzofuran-2-carboxaldehyde 2. Other known compounds including isoandrographolide, indirubin, vanillin, vanillic acid, 2(3H)-benzoxazolone, as well as beta-sitosteryl-beta-D-glucopyranoside, beta-sitosterol, and 7alpha-hydroxysitosterol were also isolated. The structures were established based on spectroscopic data and comparison with the literature. Furthermore, the compound isoandrographolide has demonstrated strong cytotoxic properties towards a panel of cancer cell lines (MCF-7, PC-3, and H-460) with the IC50 values of 7.9, 8.7, and 9.0 microM, respectively.